2014
DOI: 10.1080/23279095.2013.863775
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Degree of Effort Involved in the TOMM and the ACS Word Choice Test Using a Dual-Task Paradigm

Abstract: The aims of the current study were to: (a) examine the predictive validity and efficacy of the Advanced Clinical Solutions Word Choice Test (WCT) as a measure of effort relative to the Test of Memory Malingering (TOMM); (b) investigate whether performing a dual (distraction) task would undermine performance on either test; (c) assess the effect of coaching on the diagnostic accuracy of both the WCT and the TOMM; and (d) establish an optimal cut score for the WCT. The current study used a simulation design base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 39 publications
(92 reference statements)
1
23
0
Order By: Relevance
“…Recognition of the words is tested immediately following the learning trial using a forced-choice paradigm of a target item and a foil. Consistent with previous research, noncredible and valid performance were identified using the cutoffs of ⩽41 and ⩾42, respectively (Bain & Soble, 2019; Barhon, Batchelor, Meares, Chekaluk, & Shores, 2015).…”
Section: Methodssupporting
confidence: 76%
“…Recognition of the words is tested immediately following the learning trial using a forced-choice paradigm of a target item and a foil. Consistent with previous research, noncredible and valid performance were identified using the cutoffs of ⩽41 and ⩾42, respectively (Bain & Soble, 2019; Barhon, Batchelor, Meares, Chekaluk, & Shores, 2015).…”
Section: Methodssupporting
confidence: 76%
“…Furthermore, the CAM’s ease of implementation in comparison to clinical known groups (e.g., Greve et al, 2008) or drug administration paradigms (Loring et al, 2011) would facilitate replication by independent research groups. Of note, in the final stages of preparing this manuscript Barhon, Batchelor, Meares, Chekaluk, and Shores (2014) reported similar success in using a dual task paradigm to simulate cognitive impairment in healthy adults, further supporting the potential utility of this approach.…”
Section: Summary and A Way Forwardmentioning
confidence: 69%
“…Authors of both studies noted that their findings suggest that the WCT should not be used alone as an indicator of performance validity, but should be considered in the context of performance on multiple PVTs. In a later analogue sample study, Barhon, Batchelor, Meares, Chekaluk, and Shores (2015) compared the WCT against the Test of Memory Malingering (TOMM) in its ability to distinguish between undergraduate students instructed to provide full effort and those instructed to feign acquired brain injury (with and without coaching). Both the TOMM and WCT demonstrated good ability to discriminate between feigned CI and valid performance.…”
mentioning
confidence: 99%